The Influence Of Leadership Style Towards Employee’s Performance At UOB Buana Bank Medan - Vivian Vivian; Elyzabeth Wijaya (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
This study aims to assess the influence of leadership style on employee performance at UOB Buana Bank Medan. The significance of leadership style in influencing staff engagement, dedication, and productivity has been acknowledged. Having a comprehensive grasp of how leadership style may impact performance is crucial in the banking business, which is characterized by fierce rivalry and continuously evolving market circumstances. The research was carried out by distributing a questionnaire survey to workers from different work units at UOB Buana Bank Medan. The questionnaire was designed to evaluate the employees' perception of the leadership style employed inside the organization, as well as their level of performance. The population under investigation comprises all employees of UOB Bank Medan. The sample approach employed is simple random sampling. The sample size for this study consisted of 110 workers. The acquired data was subsequently examined utilizing statistical methodologies, such as regression, to assess the relationship between the independent variable (leadership style) and the dependent variable (employee performance). The results of this study are anticipated to offer valuable insights for UOB Buana Bank Medan in enhancing leadership approaches to enhance employee performance. The practical implication of this study is that it can aid managers in selecting a leadership style that aligns with the specific attributes of the organization.